Observing Unobservables: Identifying Information Asymmetries with a Consumer Credit Field Experiment - Dean S. Karlan; Jonathan Zinman (Yale University, Economic Growth Center, 2005)
Information asymmetries are important in theory but difficult to identify in practice. We estimate the empirical importance of adverse selection and moral hazard in a consumer credit market using a new field experiment methodology. We randomized 58,000 direct mail offers issued by a major South African lender along three dimensions: 1) the initial 'offer interest rate' appearing on direct mail solicitations; 2) a 'contract interest rate' equal to or less than the offer interest rate and revealed to the over 4,000 borrowers who agreed to the initial offer rate; and 3) a dynamic repayment incentive that extends preferential pricing on future loans to borrowers who remain in good standing. These three randomizations, combined with complete knowledge of the Lender's information set, permit identification of specific types of private information problems. Specifically, our setup distinguishes adverse selection from moral hazard effects on repayment, and thereby generates unique evidence on the existence and magnitudes of specific credit market failures. We find evidence of both adverse selection (among women) and moral hazard (predominantly among men), and the findings suggest that about 20% of default is due to asymmetric information problems. This helps explain the prevalence of credit constraints even in a market that specializes in financing high-risk borrowers at very high rates.
Keywords: C9; D8; G2; G3; O1; 330; Information asymmetries; field experiment; adverse selection; moral hazard; development finance; credit markets; microfinance; Mikrofinanzierung; Asymmetrische Information; Test; Adverse Selektion; Moral Hazard; Verbraucherkredit; Schätzung; Südafrika